Deconstructing the I and SLA in ISLA: One curricular approach - Leow, Ronald P.; Cerezo, Luis (Studies in Second Language Learning and Teaching, 2016)
Instructed second language acquisition (ISLA) has been referenced in the larger field of the SLA literature for over two and a half decades. Currently, there are several theoretical underpinnings accounting for processes assumed to play a role in ISLA and quite an impressive number of studies have empirically addressed some aspect(s) of ISLA. Recently, a lengthy and relatively cohesive treatise of this substrand of SLA research in relation to both theoretical, empirical, and pedagogical perspectives has been published in two books (cf. Leow, 2015a; Loewen, 2015), and a new model of the L2 learning process in ISLA has been proposed (Leow, 2015a). These publications are timely and important given that the concept of ISLA not only needs to be clearly defined but also situated contextually. To this end, this article (a) revisits current definitions of ISLA in the SLA literature with the aim of identifying specific features of ISLA that underlie such definitions, (b) deconstructs ISLA by probing deeper into what comprises the terms instructed and SLA in ISLA, (c) provides a brief summary of the cognitive processes and variables postulated by the theoretical underpinnings of ISLA and pertinent empirical research, (d) recommends that ISLA be observed from one curricular approach together with its empirical and pedagogical ramifications, and (e) provides some measure of direction future ISLA research may follow.